PERBANDINGAN KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS PADA PT GOTO GOJEK TOKOPEDIA TBK DAN PT BUKALAPAK.COM TBK PERIODE 2019 - 2024 - Ansari, Andre; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Financial performance is a major concern for users of financial reports. This study aims to analyze and compare the financial performance of PT GoTo Gojek Tokopedia Tbk and PT Bukalapak.com Tbk during the 2019–2024 period using liquidity, solvency, and profitability ratios. The research employs a descriptive quantitative method using secondary data from annual financial reports. The results show that both companies have good liquidity conditions, with Current Ratios above the minimum standard. In terms of solvency, both companies have a fairly healthy capital structure with controlled debt levels. However, from a profitability perspective, both companies experienced losses for most of the research period due to high operational costs and business expansion strategies. PT GoTo has shown profitability improvements since 2023, while PT Bukalapak remains in a negative trend but is gradually improving. This study concludes that although both companies face profitability challenges, their liquidity and solvency positions remain strong, supporting long-term business sustainability.